Impact of Training and Development, Corporate Entrepreneurship and Job Characteristic on Employee Retention through the Job attitude in Insurance Industry of Pakistan - Alamgir, Muhammad; Ahmed, Zujaj; Ali, Mehak (Annals of Human and Social Sciences, 2024)
This study was intended to analyze the relationship of worker’s training and development, corporate entrepreneurship and job characteristic on employee retention in insurance industry of Pakistan. Whereas, Job Attitude towards insurance industry acts as a mediator in the relationships in between training and development, corporate entrepreneurship, job characteristic and employee retention. Today employees retaining is importance for any organization because of growing competition. And they have been totally reviewed in the framework of various industries. Also, here determinants of employee’s retention explained by the integration of social exchange concept. Analysis were conducted using data from a sample of 360 slaes staff of general insurance companies in the southern Punjab, Pakistan. Data was collected through a questionnaire based on adopted scales. The instruments used to collect the data were Training and Development scale (Rogg et al. 2001) consists of 6-items. Corporate Entrepreneurship (Monsen and Boss 2009) consists of 30-items having four dimensions, innovation, risk taking, pro-activeness and entrepreneurship culture. Job Characteristic (Hackman and Oldham 1976), consists of 15-items and 5 dimensions each. Employee’s retention (Kyndt et al. 2009) et al. 2009), uni-dimensional scale having 11-items. Job attitude (porter 1974), two-dimensional i.e. job satisfaction and organizational commitment, consists of 14 items. Findings indicated that Training and development, corporate entrepreneurship and job characteristic were influence significantly in predicting employee retention through the job attitude (Job Satisfaction & Org Commitment) as a mediation. Whereas, Training and development, corporate entrepreneurship and job characteristic found having significant direct relation with employee retention. Hence, it can be recommended that from various samples set or from various populations; the same investigation can be led on cross-national on cross-country premise.